Fortifying crops with micronutrients for sustainable global nutritional security - Gautam, Ashish; Sharma, Vinay; Chauhan, Charupriya; Thakur, Anamika; Pandey, Manish K.; Priscilla, Kagolla; Dagar, Rinku; Jin, Xiaoli; Sukla, Pawan; Kumar, Anirudh; Kumar, Rakesh (American Society of Agronomy, 2025)
The adverse effects of climate change on crop productivity and nutritional content have raised concerns toward food and nutritional security. These challenges can be mitigated by developing climate-resilient and biofortified crop varieties. A biofortification strategy focused on developing cultivars enriched in essential micronutrients is one of the most promising and effective approaches to addressing nutrient deficiencies in the context of a changing climate. Current efforts by scientists around the globe are aimed at bio-fortifying crops to meet present and future nutritional security needs. The grain fortification with enhanced mineral content in the seed endosperm/cotyledon depends on several factors: the nutritional status of the soil, the bioavailability of minerals in the rhizosphere, and, more specifically, the plant's ability to efficiently uptake and transport these nutrients to the sink organs. Microorganisms play a critical role in this process by improving soil health and facilitating the breakdown of trace elements through various biogeochemical cycles. In particular, plant growth-promoting (PGP) microbes, primarily actinomycetes, enhance bioavailability of minerals to crop plants, thereby improving seed mineral content. Emerging technologies and research innovations can combat global hidden hunger, and ensure nutritional security worldwide, even amidst the challenges posed by climate change. This review highlights the importance of biofortification, addresses the imminent challenges, and suggests actionable solutions. Additionally, it explores the combination of traditional agricultural practices with modern approaches to enhance nutritional quality of crops, thus contributing to a sustainable and secure food system for the future.